2011
DOI: 10.1136/ard.2011.154815
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role for antigen-presenting cells overexpressing SOCS3 in controlling invariant NKT cell responses during collagen-induced arthritis

Abstract: Objective Suppressor of cytokine signalling (SOCS) proteins constitute a class of intracellular proteins that are key physiological regulators of immune cell function. It has previously been shown that antigen-presenting cells (APCs) overexpressing SOCS3 steer T helper immune responses and protect against experimental arthritis. A study was undertaken to investigate the contribution of SOCS3 in regulating invariant natural killer T (iNKT) cell responses during collagen-induced arthritis (CIA). Methods DBA/1 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…The SOCS adaptor proteins are in turn induced by IL-10 [15]. In fact, increased expression of both SOCS1 and 3 have been shown to decrease the severity of arthritis [15], [25], [26]. In our system, increased production of IL-10 in lymph nodes coincides with elevated mRNA levels of SOCS1 and decreased levels of IL-6.…”
Section: Discussionmentioning
confidence: 53%
“…The SOCS adaptor proteins are in turn induced by IL-10 [15]. In fact, increased expression of both SOCS1 and 3 have been shown to decrease the severity of arthritis [15], [25], [26]. In our system, increased production of IL-10 in lymph nodes coincides with elevated mRNA levels of SOCS1 and decreased levels of IL-6.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, our group showed that intravenously induced overexpression of murine SOCS-3 markedly ameliorated collagen-induced arthritis via modulation of T cell and natural killer T cell responses (8,9). The role of SOCS proteins in mediating inhibition of cytokine and growth factor responses makes the SOCS proteins prime candidates for regulating chondrocyte function during growth and joint diseases.…”
mentioning
confidence: 99%
“…These cells have been shown to produce vast amounts of IL-17 upon CD3 and IL-23 stimulation,37 and in particular, the NK1.1 − iNKT cells 38. Moreover, the iNKT cells have been shown to be important in experimental arthritis 39. Finally, the γδ T-cells have been shown to produce IL-17 in response to mycobacterium infection40 and IL-23 alone is sufficient to induce IL-17 production in these cells.…”
Section: Discussionmentioning
confidence: 99%